The experiences of physiotherapists and occupational therapists working as rehabilitation ward leaders. (2nd August 2022) - Locke, Rachel; Wilkinson, Emma; Wallis, Lucy; Kibble, Sharon; Harden, Beverley
Abstract : Background/Aims: Rehabilitation teams have piloted the deployment of physiotherapists and occupational therapists into the role of ward leader. This was the first research study designed specifically to explore the experiences of physiotherapists and occupational therapists working as ward leaders on wards with a patient rehabilitation focus and how to optimise this workforce transformation. Methods: An interpretivist qualitative study was designed to enable the detailed exploration of physiotherapists' and occupational therapists' working experiences during their time as ward leaders. A total of 11 physiotherapists and occupational therapists with between 6 months' and 3 years' experience of working as ward leaders participated in semi-structured interviews. Thematic analysis was undertaken. Results: Four themes were derived from the data analysis that related to participants' experiences: becoming a rehabilitation ward leader; responsibilities of physiotherapists and occupational therapists; perceptions of the role; and impact of allied health professionals in ward leader roles. Although taking on the role of a rehabilitation ward leader was reported as 'challenging', participants would recommend it. Success was perceived by interviewees to be relative to the presence of personal leadership qualities, the belief of the individual in their unique skill set and the confidence in the leadership team to value the unique and shared skills of the profession or individual and thus reinvent the role. Conclusions: This study identifies the key attributes that evidence the unique contribution that physiotherapists and occupational therapists working as rehabilitation ward leaders can make. The findings of this study are significant and highly relevant for the ongoing pandemic, which has seen a need for increased rehabilitation capability.